Do Financial Constraints Affect the Composition of Workers in a Firm? - Robert Breunig; Diana Hourani; Sasan Bakhtiari; Elisabetta Magnani (Institute of Labor Economics (IZA), 2020)
We study the relationship between financing constraints and the work- force composition of firms that employ both casual and non-casual workers. We use data on Australian firms from 2009-2014 and a more direct measure of firm financial constraint than previous studies. We show that the proportion of casual workers in firms grew over the time period being analysed. This was the case regardless of whether a firm was financially constrained or not. However, the magnitude of this change differed between financially constrained and unconstrained firms. We find that of firms whose workforces were growing, financially constrained firms hired relatively fewer casual workers than financially unconstrained firms did. This is consistent with firms using internal financing to cope with a lack of access to credit and equity.
Keywords: D22; L23; J29; J49; 330; financial constraints; firm behaviour; employment patterns; casual work; Australia